Supramolecular structure of stacked and unstacked regions of the photosynthetic membranes of Prochloron sp., a prokaryote - Giddings, Thomas H. (1980)
Freeze-fracture replicas of the photosynthetic prokaryote Prochloron sp., collected at Coconut Island, Hawaii, show that the thylakoids are differentiated into stacked and unstacked regions much like the thylakoids of green algae and higher plants. On the exoplasmic (E) fracture face, the particle density is greater in stacked regions (≈3100 particles/μm(2)) than in unstacked regions (≈925 particles/μm(2)). On the complementary protoplasmic (P) fracture face, the particle density is lower in stacked regions (≈2265 particles/μm(2) than in unstacked regions (≈4980 particles/μm(2)). The histogram of the diameters of E face particles in unstacked regions shows a single broad peak centered at 80 Å. In stacked regions, four distinct peaks, at 75, 105, 130, and 160 Å, are observed. These size classes are virtually identical to those found on E faces of thylakoids of the green alga Chlamydomonas and of greening pea chloroplasts. In the latter systems, the different size classes of E face particles are believed to represent photosystem II units surrounded by variable amounts of chlorophyll a/b light-harvesting complex. We propose that the same interpretation applies to the thylakoids of Prochloron, which contain a similar chlorophyll a/b complex. Our results add to the evidence supporting the view of the chlorophyll a/b complex as both a light-harvesting complex and a membrane adhesion factor. The similarity of the architecture of the thylakoids of Prochloron to that of green algal and plant chloroplasts also provides additional evidence of an evolutionary relationship between Prochloron and the chloroplasts of green plants.